2005
DOI: 10.1128/aac.49.12.5149-5152.2005
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the Klebsiella pneumoniae OKP Chromosomal Beta-Lactamase Are Divided into Two Main Groups, OKP-A and OKP-B

Abstract: Two bla OKP subgroups were found, diverging by 4.2%. Subgroups bla OKP-A (10 enzyme variants, pIs from 7.1 to 8.3) and bla OKP-B (11 variants, pI 7.1) showed similar antibiotic susceptibilities. Sequencing of rpoB, gyrA, and mdh demonstrated a concordant subdivision of Klebsiella pneumoniae phylogenetic group KpII into two subgroups, KpII-A and KpII-B.Klebsiella pneumoniae clinical isolates are naturally resistant to ampicillin, amoxicillin, carbenicillin, and ticarcillin, but not to extended-spectrum beta-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 14 publications
5
54
0
Order By: Relevance
“…The necessity of obtaining complete sequences of bla SHV, bla LEN and bla OKP genes with appropriate primer-pairs was pointed out [10,11,19]. Moreover, the phylogenetic tree that was established is in agreement with a previous report describing three major groups of sequences corresponding to the bla SHV , bla LEN and bla OKP families of β-lactamase genes [9,12,13].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The necessity of obtaining complete sequences of bla SHV, bla LEN and bla OKP genes with appropriate primer-pairs was pointed out [10,11,19]. Moreover, the phylogenetic tree that was established is in agreement with a previous report describing three major groups of sequences corresponding to the bla SHV , bla LEN and bla OKP families of β-lactamase genes [9,12,13].…”
Section: Discussionsupporting
confidence: 74%
“…It was proposed that the chromosomally encoded bla LEN and bla OKP enzymes should be grouped in a single new family "K. pneumoniae-specific chromosomal β-lactamases," excluding plasmid encoded bla SHV enzymes from this family [11]. Furthermore, it has been shown that variants of chromosomally encoded K. pneumoniae OKP β-lactamases comprise two main groups, the bla OKP-A and bla OKP-B β-lactamases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the phylogenetic analysis of the rpoB gene sequence (see Fig. S1 in the supplemental material), the 77 reference strains were attributed to K. pneumoniae (n ϭ 54), including three strains (K50, K60, and K80) corresponding to phylogenetic group KpII-B (40) wzi sequencing of K-type reference strains. wzi is one of the few genes present in the capsular polysaccharide cluster of all capsular types of K. pneumoniae.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is clear that K. pneumoniae is genetically and phenotypically diverse (12,13), previous efforts to identify specific features that can distinguish human clinical isolates from plant, animal, or environmental isolates have yielded no markers of humanspecific lineages (14). Three distinct phylogroups of K. pneumoniaeKpI, KpII, and KpIII-have been defined based on sequencing of a small number of genes (15,16), and it has been proposed that these phylogroups be redesignated as distinct species, namely, K. pneumoniae (KpI), K. quasipneumoniae (KpII) (17), and K. variicola (KpIII) (18); however, all three cause infections in humans (15,19).…”
Section: Significancementioning
confidence: 99%